2020
DOI: 10.1021/acs.est.0c04195
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Urine Diversion and Conversion to Fertilizer Products at the City Scale

Abstract: Separate collection of urine to recover nitrogen and phosphorus has been advocated to enhance the sustainability of water management and food production. Urine could provide a renewable source of nitrogen and phosphorus, which are currently extracted from nonrenewable resources. Urine diversion also has the potential to prevent nutrients from entering water bodies and to reduce the amount of energy and chemicals needed to treat wastewater. However, urine diversion would require systems to collect urine, produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 116 publications
0
33
0
Order By: Relevance
“…This also makes sense from an environmental point of view. Whereas a number of life cycle assessments have consistently shown that urine source separation is environmentally beneficial, [45][46][47][48][49] this is strongly dependent on the ability to off-set synthetic fertilizer 45 and the ability to produce a fertilizer product with low nitrogen emissions during spreading. 50 We thus observe three positive aspects of urine source separation with respect to the SDGs.…”
Section: Urine Source-separation As An Enabling Technology To Reach the Water-related Sdgsmentioning
confidence: 99%
“…This also makes sense from an environmental point of view. Whereas a number of life cycle assessments have consistently shown that urine source separation is environmentally beneficial, [45][46][47][48][49] this is strongly dependent on the ability to off-set synthetic fertilizer 45 and the ability to produce a fertilizer product with low nitrogen emissions during spreading. 50 We thus observe three positive aspects of urine source separation with respect to the SDGs.…”
Section: Urine Source-separation As An Enabling Technology To Reach the Water-related Sdgsmentioning
confidence: 99%
“…Human excreta are the primary source of essential nutrients in domestic wastewater. Urine contains an estimated 50% of P and 80% of N present in domestic wastewater while accounting for less than 1% of wastewater volume [ 7 ]. Source-separation of urine for fertilizer production can reduce the environmental impact compared to synthetic fertilizers [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urine contains an estimated 50% of P and 80% of N present in domestic wastewater while accounting for less than 1% of wastewater volume [ 7 ]. Source-separation of urine for fertilizer production can reduce the environmental impact compared to synthetic fertilizers [ 7 , 8 ]. Hilton et al [ 7 ] assessed that fertilizer production from source-separated urine could reduce greenhouse gas emissions by 47%, energy consumption by 41%, eutrophication potential by 64%, and freshwater use by 50% compared to synthetic fertilizer use.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting our study in the New England and the Upper Midwest regions enabled us to consider how both geographic location and scale of implementation will influence patterns of adoption. Several recent studies have addressed the value of urine reclamation to achieve sustainability goals, including completing nutrient cycles and reducing greenhouse gas emissions (see Hilton et al, 2021;Legrand et al, 2020;Simha & Ganesapillai, 2017). Other site-specific social studies conducted across the globe on urine diversion have emphasized different facets of the complex risks and understandings caught up in both the technological implementation and agricultural reuse of human urine.…”
Section: Introductionmentioning
confidence: 99%
“…The wider project of which our work is part explores how human urine has the potential to complete the nutrient cycle (preventing nutrient pollution and supporting sustainable agriculture) while also reducing greenhouse gas emissions (Hilton et al, 2021). 1 From the wastewater perspective, urine contributes approximately 75% of the nitrogen and 50% of the phosphorus in domestic wastewater (Vinnerås, 2006), nutrients which are rarely removed before their discharge into waterways, resulting in nutrient pollution that contributes to harmful algal blooms.…”
Section: Introductionmentioning
confidence: 99%